KOLOKIAL DAN ARGOT DALAM ACARA INDONESIA LAWAK KLUB (ILK): KAJIAN SOSIOLINGUISTIK DAN SEMANTIK - Rezki Hasanah; Mangatur Sinaga; Hermandra Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This study discusscolloquial and argot in Indonesian LawakKlub (ILK) TV Show based of the form and meaning of the words uttered by the ILK participants. The research was conducted using qualitative approach and descriptive method to describe the form and meaning of the words from the colloquial and argot used by the participant of the ILK TV Show. The subjects of this research were 3 episodes of ILK TV Show. The data of the research was the discourse delivered by the participant of ILK TV Show. The data was collected using recording and noting technique which were classified based on the form of the colloquial and argot. Based on the results of the research, it can be concluded that in the ILK TV Show, there were several forms of colloquial and argot. Moreover, there were also several vocal and consonant omissions as well assome removals of the last syllable of the words. The forms of colloquial founded were: (1) colloquial using the basic word, (2) colloquial in which thevowel a is omitted, (3) colloquial in which the vowel i is omitted, (4) colloquial in which the vowel e is omitted (5)colloquial in which the consonant h is omitted(6) colloquial in which the consonant s is omitted, (7) colloquial in which the vowel e and the consonant ng are omitted, (8) colloquial in which the consonant b and vowel a are omitted, (9) colloquial in which the consonant b and vowel e is omitted, (10) colloquial in which the consonant k and vowel a is omitted, (11) colloquial in which the last syllable is omitted. In addition, the forms of argot founded wereargot using the basic word and argot using the affixes.Keywords: Colloquial and Argot, Form, Indonesia LawakKlub (ILK)